C04 Green2Gold: Piloting ‘Team GB Family Activity Trails’ as a green exercise project for improving wellbeing and outdoor physical activity engagement in the East Riding of Yorkshire - Carter, Esther; Douglas, Caroline; Saxton, John (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Systematic review evidence suggests that participation in green exercise (GE; Coventry et al., 2021, SSM-Population Health, 16, 100934) including walking (Hanson and Jones, 2015, Brit J Sports Med, 49, 710-715) can positively impact health and wellbeing. The aim of the project, titled ‘Green2Gold’, was to collaborate with The British Olympic Association to co-create ‘Team GB Family Activity Trails’, a novel GE intervention, in two locations. Signposts were installed along the walking routes containing co-designed activities linked to Olympic sports, physical activity (PA), and nature. Each signpost contained a unique QR code to provide users with additional PA and education opportunities on the project’s website. The purpose of this study was to assess the impact of trail engagement on health, wellbeing, and physical activity outcomes. An a priori power analysis (G*Power 3.1) using small effect sizes suggested a sample size of at least 34 participants. With institutional ethical approval, 37 participants age 5+ were recruited to test the trails three times within a six-week period, using a within-subjects repeated-measures experimental design. Pre- and post-intervention changes in perceived health, mental wellbeing, and PA and nature engagement were collected and analysed using Wilcoxon signed-rank tests. Additional post-intervention feedback on enjoyment, motivators, and barriers were collected, with frequencies and crosstabulations calculated. In-the-moment changes in perceived health, mental wellbeing, and enjoyment were measured before and after each walk and compared using two-way repeated measures ANOVAs. Analyses were conducted using JASP software (v18.1). Single-item scores for general health (P < .001), measures of mental health (P = 0.006 to 0.015), and number of days engaging in nature (P = .004) improved for both adults and children. Furthermore, significant pre-to-post intervention improvements in the perceived value of exercise and being outdoors (P = 0.015 to 0.031) and the number of days walking per week (P = 0.034) were reported for adults, with children demonstrating significantly improved future PA intention (P = .043). Overall, a significant effect of ‘Time’ was present for measures of perceived physical and mental health, fitness, nature connection, and feelings of inspiration (P < 0.05) when assessed from pre-to-post walk on three occasions. No significant effect for ‘Walk*Time’ was present. The study provides preliminary evidence to support ‘Activity Trails’ endorsed by a well-recognised sporting body, such as an Olympic Association, as a free, self-directed activity to elicit positive perceived health, mental wellbeing, and nature engagement outcomes at a community level, with potential scalability options to other greenspaces in the UK.